Chemical attributes in a Xanthic Ferralsol under different tillage systems - Campos, Liliane Pereira; Leite, Luiz Fernando Carvalho; Maciel, Giovana Alcântara; Iwata, Bruna de Freitas; Nóbrega, Júlio César Azevedo (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the chemical attributes in a Xanthic Ferralsol under different tillage systems in the cerrado of Piauí State, Brazil. Four tillage systems were evaluated: three‑year‑old conventional tillage; no‑tillage with three (NT3) and five years old (NT5), using millet as cover crop; and no‑tillage with nine years old (NT9), of which seven years used millet as cover crop and two used forage. A native cerrado area was taken as reference. Soil samples were collected in wet and dry seasons at soil depths, 0.00–0.05, 0.05–0.10, 0.10–0.20 and 0.20–0.40 m, and analyzed for pH, Al3+, H+Al, Ca2+, Mg2+, K+, sum of bases (SB), effective (t) and potential (T) cation exchangeable capacity, base (BS) and Al3+ saturation (m%), available P and total organic carbon (TOC). The system NT9 showed the highest values of pH and lowest of Al3+, H+Al, and m%. The highest values for Ca2+, K, SB, t, T, V% and P, were observed under NT5 and NT9, until 0.20 m depth. The highest TOC contents were verified also under NT5 and NT9, except for 0.00‑0.05 m soil depth. Organic matter accumulation associated with pasture under no‑till increases TOC content at deeper soil layers in the dry period.